Nanoporous silicon fiber networks in a composite anode for all-solid-state batteries with superior cycling performance - Mari Yamamoto; Mika Takatsu; Ryota Okuno; Atsutaka Kato; Masanari Takahashi (Scientific Reports, 2023)
Abstract All-solid-state batteries comprising Si anodes are promising materials for energy storage in electronic vehicles because their energy density is approximately 1.7 times higher than that of graphite anodes. However, Si undergoes severe volume changes during cycling, resulting in the loss of electronic and ionic conduction pathways and rapid capacity fading. To address this challenge, we developed composite anodes with a nanoporous Si fiber network structure in sulfide-based solid electrolytes (SEs) and conductive additives. Nanoporous Si fibers were fabricated by electrospinning, followed by magnesiothermic reduction. The total pore volume of the fibers allowed pore shrinkage to compensate for the volumetric expansion of Li12Si7, thereby suppressing outward expansion and preserving the Si-SE (or conductive additive) interface. The network structure of the lithiated Si fibers compensates for electronic and ionic conduction pathways even to the partially delaminated areas, leading to increased Si utilization. The anodes exhibited superior performance, achieving an initial Coulombic efficiency of 71%, a reversible capacity of 1474 mAh g−1, and capacity retention of 85% after 40 cycles with an industrially acceptable areal capacity of 1.3 mAh cm−2. The proposed approach can reduce the constraint pressure during charging/discharging and may have practical applications in large-area all-solid-state batteries.